2021
DOI: 10.3389/fphar.2021.617265
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation to Support Phase Ib/IIa Dose Selection for WBP216, A Long Half-Life Fully Human Monoclonal Antibody Against Interleukin-6

Abstract: WBP216 is an innovative IL-6 antibody, presenting high affinity to IL-6 and a long half-life (40–60 days). To optimize the dosage regimen for future clinical trials, pharmacokinetics (PK) and pharmacodynamics (PD) of WBP216 would be firstly characterized in Chinese rheumatoid arthritis (RA) patients. PK, CRP and DAS28 data of WBP216 were collected from 26 RA patients in a single ascending dose study. Non-linear mixed effects modeling was used for a population PK/PD analysis. A two-compartment model with a sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The strong affinity of WBP216 prevents the interaction between IL-6 and its receptor, thereby reducing the proinflammatory activities. In addition WBP216 can directly inhibit the production of Creactive protein (CRP) and erythrocyte sedimentation rate (ESR) resulting in an improvement in the swollen and tender joints in patients with RA (19). Preclinical studies demonstrated a higher affinity of WBP216 for IL-6 receptors and a longer halflife compared to other IL-6 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The strong affinity of WBP216 prevents the interaction between IL-6 and its receptor, thereby reducing the proinflammatory activities. In addition WBP216 can directly inhibit the production of Creactive protein (CRP) and erythrocyte sedimentation rate (ESR) resulting in an improvement in the swollen and tender joints in patients with RA (19). Preclinical studies demonstrated a higher affinity of WBP216 for IL-6 receptors and a longer halflife compared to other IL-6 inhibitors.…”
Section: Introductionmentioning
confidence: 99%